Production and impact of Italian researchers in physical—Sport education and sport pedagogy - D'Elia, Francesca; D'Isanto, Tiziana; Aliberti, Sara; Ceruso, Rosario; Esposito, Giovanni; Raiola, Gaetano (Frontiers in Research Metrics and Analytics, 2025)
IntroductionIn Italy, legislation in Exercise and sports sciences (ESS) had significant progress, particularly in physical and sport education, as well as sport pedagogy for compulsory teaching of Physical education by master's degree' specialist teachers, for the new profession of kinesiologist and, first the reform of Italian Constitution about social and educational value of movement and sport. The aim of this study was to measure the specific scientific output in ESS and its impact on the scientific community.MethodsData on global scientific production related to the keywords “Physical education,” “Sport education,” and “Sport pedagogy” were extracted from the Scopus database, including total citations and h-index. Trends among Italian researchers were also examined. Data on the overall scientific output and specific trends of Italian researchers were extracted, along with total citations and h-index. The trends of total and relative metrics (citations and h-index) for the period 2020–2023 were evaluated using Spearman's correlation.ResultsAnalysis of global scientific production on Scopus revealed 31 ESS faculty members (7 full professors, 15 associate professors and 9 researchers) for “Sport Education” keyword, 11 ESS faculty members (2 full professors, 5 associate professors, and 4 researcher) for “Sport Pedagogy,” and 18 ESS faculty members (7 full professors, 7 associate professors and 4 researcher) for “Physical Education.” Less than half of these researchers are directly framed with ESS. However, despite this minority representation, significant positive correlations emerged between total citations and total H-index for the period 2020–2023 (rs = 0.83), relative citations and relative H-index (rs = 0.61), relative citation and total H-index (rs = 0.32).ConclusionsThe positive correlation found between relative citations and the total h-index indicated these scholars had a greater impact with studies relevant to the identified keywords compared to other general topics. The analysis also highlighted the lack of international impact of Italian research in the educational and didactic aspect of ESS, particularly for “Physical Education.”